1949
DOI: 10.1172/jci102184
|View full text |Cite
|
Sign up to set email alerts
|

Chloramphenicol (Chloromycetin), an Antibiotic. Pharmacological and Pathological Studies in Animals 123

Abstract: Chloramphenicol is an antibiotic which initially was isolated from culture filtrates of the fungus Streptomyces venezuelae (1-3) by Bartz (4) and subsequently was synthesized chemically (5-7).Chloramphenicol ( Material for this study consisted of crystalline chloramphenicol obtained from culture filtrates, and the synthetic product.Chloramphenicol was administered intravenously in aqueous propylene glycol or acetamide solutions to small animals at a rate of 0.1 cc. per ten seconds; dogs received 1.0 to 3.0 cc.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
2
1

Year Published

1950
1950
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 6 publications
1
21
2
1
Order By: Relevance
“…Although neither Shelesnyak (1957) nor Spaziani & Szego ( 1959) observed damage to the uterus after the administration of antihistamines, their inhibitory action may be referable to gross damage at the biochemical level. Such a possibility is indicated by the present results and by those of Gruhzit & Fisken (1947), who found severe ulcération at the site of injection of 1 % solutions of Benadryl. In addition, in the experiments of Shelesnyak (1957), and in those of Spaziani & Szego (1959), the doses of antihistamines administered per kilogram of tissue exceed by up to twentyfold the LD 50 acute toxicity levels for the rat .…”
Section: Discussionsupporting
confidence: 71%
“…Although neither Shelesnyak (1957) nor Spaziani & Szego ( 1959) observed damage to the uterus after the administration of antihistamines, their inhibitory action may be referable to gross damage at the biochemical level. Such a possibility is indicated by the present results and by those of Gruhzit & Fisken (1947), who found severe ulcération at the site of injection of 1 % solutions of Benadryl. In addition, in the experiments of Shelesnyak (1957), and in those of Spaziani & Szego (1959), the doses of antihistamines administered per kilogram of tissue exceed by up to twentyfold the LD 50 acute toxicity levels for the rat .…”
Section: Discussionsupporting
confidence: 71%
“…The adult LD50 on the basis of milligrams per kilogram is 5.3 times as high as for newborns. Gruhzit et al 10 reported the LD50/14 in an unspe¬ cified strain of adult white mice, using a single I.P. injection as 1,320 mg. per kilogram.…”
Section: Resultsmentioning
confidence: 99%
“…Its presence in the bile after an interval of two hours has been reported by Gruhzit, Fisken, Reutner, and Martino (1949), by Glazko, Wolf, and Dill (1949), and by Long, Bliss, Schoenbach, Chandler, and Bryer (1950). In the following paper some details are given of its excretion in the bile.…”
mentioning
confidence: 68%